Influência da atividade das mataloproteinases 2 e 9 na diminuiçao o colágeno tipo I miocárdico em ratos obesos - Silva, Danielle Cristina Tomaz da [UNESP] (2013)
Obesity is a chronic metabolic disorder characterized by excessive adipose tissue accumulation in relation to lean tissue. Currently, it is a global epidemic and a major public health problem that affects both developed as well as undeveloped countries. The adipocyte receives influence of several substances and secretes numerous peptides, such as leptin, angiotensin I and II, TGF-β, among others, that act directly or indirectly on the cardiovascular system. Thus, adipose tissue is not simply an energy reservoir, but an active endocrine, paracrine and autocrine organ with multiple functions, able to synthesize and release mediators that participate in many biological processes, including those that occur in the heart. The heart is composed of myocytes, nerves, vessels and extracellular matrix. The main component of matrix is collagen, predominantly type I and III, being type I the most abundant, corresponding to approximately 80% of total myocardial collagen. Collagen is mainly produced by fibroblasts and degraded by metalloproteinases (MMPs). Collagen, in a stable condition, contributes to the maintenance of cardiac architecture and function, however, in response to stimuli triggered by neuro-hormonal and/or mechanical agents, it may change, and this change can be due to increased synthesis and/or decreased degradation, or vice versa. In recent research conducted in our laboratory, we found decreased protein levels of myocardial type I collagen in obese Wistar rats by unsaturated high-fat diet for 30 weeks. Due to the results found in our laboratory and because the literature shows that leptin increases MMP-2 activity and MMP-9 gene expression, the purpose of this study was to test the hypothesis that the reduction of myocardial type I collagen is associated with increased MMPs 2 and 9 activities in obese rats by unsaturated high-fat diet. Thirty-day-old male Wistar rats were randomized into to two groups: control ...